Safety and efficacy of very short dual antiplatelet therapy followed by P2Y12 inhibitor monotherapy in older patients undergoing percutaneous coronary intervention: meta-analysis of randomised controlled trials. (22nd March 2021) - Roule, Vincent; Lemaitre, Adrien; Pommier, Wilhelm; Bignon, Mathieu; Sabatier, Rémi; Blanchart, Katrien; Beygui, Farzin
Abstract: Background: older patients undergoing percutaneous coronary intervention (PCI) represent a growing population sharing both a high ischemic and bleeding risk. Dual antiplatelet therapy (DAPT) reduces the incidence of thrombotic events but exposes patients to an increased risk of bleeding and subsequent mortality. Its optimal duration after PCI remains unclear. Objective: to assess the impact of short-duration DAPT on both bleeding and ischemic events in the specific population of older patients undergoing PCI. Methods: we performed a meta-analysis of randomised controlled trials comparing the safety and efficacy of standard versus very short duration (≤ 3 months, followed by P2Y12 inhibitor monotherapy) DAPT after PCI with a drug-eluting stent in older patients. Results: four studies, representing 8, 961 older patients, were finally included. Compared with standard duration, short-duration DAPT was associated with similar rates of major bleeding (relative risks, RR 0.70 [0.47; 1.05]) and the composite efficacy endpoint (RR 0.85 [0.63; 1.14]). There was a high level of heterogeneity between the studies ( I 2 = 68%) regarding major bleeding. Conclusion: our meta-analysis suggests that short DAPT may be a valid option in older patients after PCI but it also highlights the need for specific studies in such patients on optimal duration of antiplatelet therapy.